- Thread starter
- #1

#### Petrus

##### Well-known member

- Feb 21, 2013

- 739

Hello MHB,

solve this system of linear differential equation

\(\displaystyle f'=f-g-h\)

\(\displaystyle g'=-f+g-h\)

\(\displaystyle h'=-f+g+h\)

with boundary conditions \(\displaystyle f(0)=1\), \(\displaystyle g(0)=2\) and \(\displaystyle h(0)=0\)

we get that \(\displaystyle \lambda=1\) and \(\displaystyle \lambda=0\)

now for eigenvector or we can call it basis for eigenvector \(\displaystyle \lambda=0\) i get

Is that correct?

Regards,

\(\displaystyle |\pi\rangle\)

solve this system of linear differential equation

\(\displaystyle f'=f-g-h\)

\(\displaystyle g'=-f+g-h\)

\(\displaystyle h'=-f+g+h\)

with boundary conditions \(\displaystyle f(0)=1\), \(\displaystyle g(0)=2\) and \(\displaystyle h(0)=0\)

we get that \(\displaystyle \lambda=1\) and \(\displaystyle \lambda=0\)

now for eigenvector or we can call it basis for eigenvector \(\displaystyle \lambda=0\) i get

Is that correct?

Regards,

\(\displaystyle |\pi\rangle\)

Last edited: